(3GdJYdd hGdGWaG dfGQ dG JWaGs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd YHO GdQMef Hf CHj HcQ GdSjhWj GdMeO ddg GdPj dG QGO dbVGFg hHYO agPG cJGH ChOYJg GdCMGOjK GdhGQOI aj ehJ GdChdGO hSejJg GdJYdd hGdGWaG dfGQ dG JWaGs
(3BNQgG (B:s
(3ceG bGd JYGdi (B: { (3EfeG fYO dge YOG (B} (3EfeG gh YOO GdfaS BNQ GdLRAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 425s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs